CITIZENSHIP, POLITICAL RIGHTS AND CLASS CONSCIOUSNESS. THE DEBATE ON THE NATURALIZATION OF FOREIGNERS IN EARLY ARGENTINE SOCIALISM - Poy, Lucas (2015)
By the end of the nineteenth century and the beginning of the twentieth, Argentina was experiencing a major economic growth based on the export of raw materials and the arrival of foreign capital. It was combined with a restrictive political regime characterized by fraudulent practices and low voter turnout. Although legislation granted universal suffrage for all male Argentine citizens, the existence of a large proportion of immigrants made the issue of political participation of foreigners a crucial one. Based on an extensive analysis of the party press, this paper analyzes the way in which the issue of naturalization of foreigners was addressed by the Argentine Socialist Party since its foundation. It is argued that it appeared as an essential part of the party’s electoral strategy but also represented a demonstration of class consciousness by workers themselves that should be encouraged and stimulated. In turn, we explain how this appeal for naturalization soon faced many problems, related to the worker’s reluctance to give up their original nationality in order to obtain political rights which appeared to them of little obvious utility. After 1902, these problems were also related with the imposition of various bureaucratic and legal obstacles following the “Ley de Residencia” repressive measures.